Majmūʿa-yi rasāʾil : ʿAjāʾib aḥkām Amīr al-Muʾminīn, Dhikr al-khalāʾif wa-ʿunwān al-maʿārif, Faḍl al-ʿilm, Dhakhāʾir al-ḥikma, Mukhtaṣar-i Jāvidān khirad - Miskawayh, Ibn, (Miras Maktoob, ISBN: 9789004365452., 2019)
Today most oriental manuscript collections are kept in institutional and other (semi-) public libraries. Yet many of these collections were jumpstarted with the acquisition or donation of some private collection. Even now, private collections may still yield unexpected finds. A case in point is MS Tehran, National Library, Arabic 16574. This manuscript belonged earlier and until 1423/2002 to Sayyid Muḥsin Amīn ʿĀmilī, author of the famous biographical dictionary Aʿyān al-Shīʿa , and then to his son Sayyid Ḥasan Amīn, after whose death it devolved to the National Library of Iran. Compiled in 420/1029, this manuscript contains six medium-sized classical texts in Arabic from before ca. 390/1000. From among these, special mention must be made of an abbreviated version ( mukhtaṣar ) of Ibn Miskawayh's (d. 421/1030) gnomological work in Arabic, the Jāvidān khirad . Copied while Ibn Miskawayh was still alive, this abbreviation represents the oldest sample of the original text and certainly merits consideration in any future edition.